UPAYA MENINGKATKAN KEMAMPUAN PRAMEMBACA PADA ANAK USIA 4–5 TAHUN MENGGUNAKAN MEDIA PERMAINAN KARTU DI SPS DAHLIA 79 - Widianti Primasari; Ianatuz Zahro; Trio Suwargono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pre-reading skills are the initial skills in recognizing letter symbols, understanding the relationship between sounds and letters, and building a foundation for literacy before children learn to read formally. Introducing reading for early childhood requires a fun and engaging method to understand the letters, numbers, or symbols being presented. An educator can use many methods to develop aspects of early childhood language development so that children do not get bored easily. Based on initial observations conducted by researchers at SPS Dahlia 79 Kalisat-Jember, some children still have difficulty recognizing the alphabet and numbers, distinguishing initial sounds, and are less interested in activities related to reading. This phenomenon emerged during the learning process in class, where when the teacher sang the alphabet symbols